(untitled) (WidyaAmrita: Jurnal Manajemen, Kewirausahaan dan Pariwisata, 2026)
The performance of ASN employees of a government agency plays a very important role in providing the best image and service to the community, one of the factors that can affect the performance of ASN employees at the Bali Customary Community Advancement Service is human resource competence, utilization of information technology and good communication between fellow ASN employees. The number of samples in this study was 40 respondents who were ASN employees at the Bali Customary Community Advancement Service. The analysis technique used was multiple linear regression analysis with the SPSS Ver 26 application. The results of this study showed that human resource competence had a positive and significant effect on the performance of ASN employees at the Bali Customary Community Advancement Service. The utilization of information technology had a positive and significant effect on the performance of ASN employees at the Bali Customary Community Advancement Service. Communication had a positive and significant effect on the performance of ASN employees at the Bali Customary Community Advancement Service. In addition, the results of the F test also showed that human resource competence, utilization of information and communication technology had a positive and significant effect on the performance of ASN employees at the Bali Customary Community Advancement Service.